Feasibility analysis and suitability mapping for mitigation technologies enable targeted technology dissemination in Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
IRRI has developed a model to assess the suitability of AWD+ (in which a number of climate-smart agricultural practices are adopted in addition to AWD) in different geographical areas, using climate, precipitation, and soil data. Initial assessments conducted in Vietnam, together with the Institute of Agricultural Environment (IAE), identified suitable areas for AWD+ dissemination in the country.